Moral Disengagement and Aggression: The Mediating Role of Empathy Deficits - Chen, Liang; Chen, Mei-Ling (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the mediating role of empathy deficits in the relationship between moral disengagement and aggression among young adults. Methods and Materials: A descriptive correlational design was employed, involving 399 participants from Taiwan, selected based on the Morgan and Krejcie sample size table. Participants completed validated self-report measures: the Aggression Questionnaire (AQ), the Moral Disengagement Scale (MDS), and the Basic Empathy Scale (BES). Pearson correlation analysis was conducted using SPSS-27 to examine bivariate relationships among the variables, and Structural Equation Modeling (SEM) was employed via AMOS-21 to test the hypothesized mediation model. Model fit indices and standardized path coefficients were calculated to assess the strength and validity of the relationships. Findings: Results revealed that moral disengagement was positively correlated with aggression (r = .48, p < .001) and empathy deficits (r = .59, p < .001), while empathy deficits also correlated significantly with aggression (r = .55, p < .001). The SEM analysis confirmed that the model had acceptable fit indices (χ²/df = 2.06; CFI = .96; RMSEA = .052). Moral disengagement had a significant direct effect on aggression (β = .28, p < .001), as well as an indirect effect through empathy deficits (β = .18, p < .001), resulting in a total effect of β = .46 (p < .001). Empathy deficits also directly predicted aggression (β = .37, p < .001). Conclusion: The findings support a mediational model in which empathy deficits partially explain the relationship between moral disengagement and aggression. These results highlight the cognitive and emotional mechanisms underlying aggressive behavior and underscore the importance of targeting both moral reasoning and empathic responsiveness in intervention efforts.